The Impact of International Diplomacy on Combating Global Terrorism - Nwala, Paul (Journal of Contemporary International Relations and Diplomacy, 2023)
Insecurity had defined the global arena with insurgency and terrorism increasing by leaps and bounds. Therefore, defining terrorism as a discrete international crime under the purview of international law normatively recognizes and protects vital international community values and interests. The issue of terrorism symbolically expresses community condemnation, and stigmatizes offenders. In proper analysis context the paper opines that any definition of terrorism also accommodates reasonable claims to political violence, particularly against repressive governments, and this paper examines the range of exceptions, justifications, excuses, defenses, and amnesties potentially available to terrorists, as well as purported exceptions such as self-determination struggles. The paper further seeks to minimize recourse to violence, it recognizes that international law should not become complicit in oppression by criminalizing legitimate forms of political resistance and instead diplomacy can be applied in such scenario. In the absence of an international generally accepted definition of terrorism, the paper explores how the international community has responded to terrorism in international and ‘regional’ treaties, the United Nations system, and in customary law which has proof that diplomacy is a vital instrument in the global combat of terrorism. The conclusion of the paper explores the distinctive prohibitions and crime of ‘terrorism’ in armed conflict under international humanitarian law.